Molecular insights into the biodiversity of freshwater red macroalgae in Indonesia - Ganies Riza Aristya; Nugroho Rizki Adi Rifat; Chasani Razaq Abdul (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Many Asian countries, including Indonesia, have experienced negative effects from pollution brought on by industrialization and modernization, which have harmed freshwater ecosystems as well as natural habitats. Red macroalgaeand other creatures that depend on these ecosystems for their survival may suffer as a result, which could increase the strain on freshwater ecosystems and resources. Due to freshwater red macroalgaeare primary producers in their own ecosystems, they are essential to the cycling of nutrients and the preservation of water quality. The objective of this study is to evaluate freshwater red macroalgae in Indonesia utilizing various approaches particularly emphasis on DNA barcoding. As a result, molecular methods like DNA barcoding are employed to uncover hidden species and elucidate the evolutionary connections between different taxa, thereby exposing the diversity of red macroalgae. It is anticipated that the outcomes will yield data for further research.Keywords:DNA barcodeFreshwaterHidden speciesMolecularRed macroalgae